IMF Staff papers, Volume 39 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1992)
This paper focuses on exchange rate economics. Two main views of exchange rate determination have evolved since the early 1970s: the monetary approach to the exchange rate (in flexible-price, sticky-price, and real interest differential formulations); and the portfolio balance approach. In this paper, the literature on these views is surveyed, followed by a discussion of the empirical evidence and likely future developments in the area of exchange rate determination. The literature on foreign exchange market efficiency, exchange rates and 'news,' and international parity conditions is also reviewed.